Experiencing absurdity of organizational life: a dive in a kafkaesque universe - Matos, Lorena Bezerra de Souza (2018)
Dysfunctional bureaucracy is a major challenge for developing countries like Brazil today. There are innumerable problems, among which the lack of effectiveness, inefficiency, and absurd contexts that lead to stress, suffering and burn-out are highlighted. Although such organizations have received attention from the area of Administration and Organizational Studies, the studies related to coping with absurd contexts are very incipient. More rare are the empirical studies that analyse the daily life of people who face such situations. In order to address such gaps, this research is based on an empirical study carried out in a 15-month period (October 2015 to December 2016) of data collection through 50 interviews, conversations and daily observation of managers of research, development and innovation (R&D&I) projects in the largest company in the electric sector in Brazil. Secondary data and documents were also collected. The goal of this research is to develop theory about the absurd in bureaucratic organizations. This research contributes to the development of academic knowledge in two aspects: first, from the theoretical point of view, when dealing with absurdity in a bureaucratic organizational context, a subject not much discussed; second, from a practical point of view, to deepen the knowledge about the daily life of managers, and to bring elements that allow to rethink several of the daily challenges of these managers. Data was analyzed through an iterative thematic analysis. Through this I identified that the organizational context is complex and involves: (1) Bureaucracy; (2) Multiples cultures; (3) Leadership changes and the lack of sensegiver; (4) R&D&I colliding with organizational routine; (5) Personality in the processes; (6) Informality and non-registration of activities; (7) Politics. The data theory presents that the absurd is understood from the notions of: (a) Environment of contradictions; (b) Fear and guilt; and (c) Loneliness. The consequences of the absurd experience in the context studied involve: (i) Emotional work; (ii). Turnover; (iii) Non-implementation of projects; (iv) Metamorphosis of the sense of innovation; (v) Loss of sense of innovation; and (vi) Inaction. In answering the proposed research question, the contributions of this thesis are: (i) the elaboration of a working definition for absurdity; (ii) contribution to the practice of innovation management in the Brazilian electric sector, based on the reflection of its innovation dynamics. The theory generated is under construction and reflects the interpretation of a particular researcher. The effort of this research is expected to stimulate researchers in the continuity of research into the absurd in bureaucratic organizations.